2014
DOI: 10.1111/ncmr.12042
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Communication and Worker Perceptions of Conflict Management and Justice

Abstract: Organizations are well advised to develop a conflict culture promoting constructive conflict management and cooperation. But what does such a culture look like? Research from international and political relations has demonstrated that the level of integrative complexity (IC) as disseminated in political messages is an important factor in the context of conflict management. In our research, we hypothesize that, similar to political messages, corporate communication, which emphasizes a complex (i.e., differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 101 publications
0
4
0
1
Order By: Relevance
“…Presumably, complex tasks in complex and dynamic environments require complex thinking (Lord et al, 2011; Satish, 1997) and, as argued here, complex group interaction modes that allow for both differentiation and integration in an intertwined manner. The concept of IC also poses a methodological asset for future research, as it allows coding any kind of written or verbal statements, be they individually or collectively produced (for another example, see Kugler & Brodbeck, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, complex tasks in complex and dynamic environments require complex thinking (Lord et al, 2011; Satish, 1997) and, as argued here, complex group interaction modes that allow for both differentiation and integration in an intertwined manner. The concept of IC also poses a methodological asset for future research, as it allows coding any kind of written or verbal statements, be they individually or collectively produced (for another example, see Kugler & Brodbeck, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of IC on dealing with differences and dissent have also been studied in the field of organizational psychology. High levels of IC helped expatriates use their diverse experiences gathered abroad for innovative outcomes (Tadmor, Galinsky, & Maddux, 2012), and organizational cultures exhibiting high levels of IC were found to be associated with more constructive conflict management within the organization (Kugler & Brodbeck, 2014).…”
Section: Integrative Complexity (Ic)mentioning
confidence: 99%
“…Research has repeatedly shown that lower in comparison with higher levels of integrative complexity are associated with increases in conflict escalation (Suedfeld & Leighton, 2002;Tetlock, 1985), aggressive acts (Satterfield, 1998), competitive strategies (Kugler & Brodbeck, 2014;Walker & Watson, 1994), tension and stress (Suedfeld, 1992;, violence (Suedfeld, Tetlock, & Ramirez, 1977), and international crises (Ballard, 1983;Suedfeld & Bluck, 1988;. In contrast, higher levels of integrative complexity have been shown to be related to more cooperative agreements, peaceful resolutions (Koo, Han, & Kim, 2002;Liht, Suedfeld, & Krawczyk, 2005;Winter, 2007) and constructive inter-and intra-group processes (Brodbeck, Kugler, Fischer, Heinze, & Fischer, 2020;Park & DeShon, 2018).…”
Section: Research Parameters For Assessing Complexity In Potentially mentioning
confidence: 99%
“…Tällöin ristiriidan mainingeilla on taipumus levitä, jolloin se alkaa viedä huomiota ja syödä työaikaa ja voimavaroja yhä isommalta työntekijäjoukolta. Alentuneen tuottavuuden lisäksi puuttumattomuus värittää yksilöiden kokemusta organisaation ja johtamisen oikeudenmukaisuudesta ja ennustaa työn sujumista tulevaisuudessakin (Kruger & Brodbeck 2014). Olennaista ei ole se mistä riidellään, vaan se, miten ongelmat ratkotaan (DeChurch 2001).…”
Section: Vuorovaikutus Työhyvinvoinnin Perustanaunclassified